Transportasi Online: Analisis Bibliometrik dan Systematic Literature Review (SLR) - Dea Rizka Koesalia; Keisha Nathaya Yona Wirawan (Jurnal Sains dan Teknologi, 2026)
Online transportation has become an essential component of modern urban mobility, significantly transforming the way people travel while creating new challenges related to service quality, safety, customer satisfaction, sustainability, and its impact on conventional public transportation. This study aims to examine the development of research on online transportation through a bibliometric analysis combined with a Systematic Literature Review (SLR). Data were collected from the Scopus database using the keyword "Online Transportation" and filtered using the PRISMA framework, resulting in 90 eligible articles for analysis. The bibliometric analysis was conducted using VOSviewer to identify publication trends, leading contributing countries, author affiliations, journal sources, and the most frequently occurring keywords. The findings reveal that research on online transportation remains relatively limited despite showing a gradual increase in recent years. Indonesia emerged as the country with the highest number of publications, followed by the United States, China, Japan, Malaysia, and the United Kingdom. Frequently occurring keywords indicate that online transportation research is commonly associated with traffic management, drivers, passenger safety, customer satisfaction, service quality, employment, and user loyalty. These findings suggest substantial opportunities for future studies, particularly in the areas of regulatory frameworks, sustainable transportation, traffic safety, digital technology integration, and the development of intelligent transportation systems to support more efficient, inclusive, and sustainable urban mobility.